Mass Fragmentation Characteristics of t-Boc Substituted Drug Precursors - Cui-mei LIU; Xue-yan LIU; Zhen-dong HUA; Hao TANG; Yu DU; Wei JIA (Zhipu Xuebao)
To circumvent the supervision of law, illicit manufacturers turn to produce drug related precursors. Among them, tert-butoxycarbonyl (t-Boc) substituted drug precursors are the most common type recently. The t-Boc moiety is a common protecting group in organic synthesis. It can prevent a chemical reaction at one specific group in a molecule, while other functional groups are transformed, and then can be easily chemically removed through a simple carbamate hydrolysis. Due to the lack of control, the readily availability from chemical suppliers, and easy conversion to an immediate, these t-Boc substituted precursors are attractive to illicit manufacturers. The identification of these newly emerging precursors has posed great challenges to forensic science laboratories worldwide. In this study, four types of t-Boc substituted drug precursors, including tert-butyl 4-(phenylamino)piperidine-1-carboxylate (t-Boc-4-AP), tert-butyl 4-((4-fluorophenyl)amino)piperidine-1-carboxylate (t-Boc-4F-AP), tert-butyl 4-((4-bromophenyl)amino)piperidine-1-carboxylate (t-Boc-4Br-AP), and tert-butyl (1-(2-chlorophenyl)-2-oxocyclohexyl)carbamate (t-Boc-norketamine), were analyzed by using gas chromatography-mass spectrometry (GC-MS) and ultra-high performance liquid chromatography-quadrupole time of flight-mass spectrometry (UPLC-QTOF MS). After analyzing the characteristic fragment ions under electron impact (EI) mode and electrospray ionization collision-induced dissociation (ESI-CID) mode, the possible fragmentation pathways of t-Boc substituted drug precursors were deduced. The main product ions of t-Boc substituted drug precursors are tert butyl ion (C4H9+), and product ions of [M−C4H8]+, [M−C4H9O•]+, and [M−C5H8O2]+ under EI mode. Under ESI-CID mode, product ions are mainly formed by the loss of C4H8 and the further loss of CO2. The study of the fragmentation pathways of t-Boc substituted drug precursors in mass spectrometry benefits the structure elucidation of unknown compounds, and provides reference for forensic science laboratories to identify such substances.